2023
DOI: 10.1097/mat.0000000000001889
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban Anticoagulation in Children and Young Adults Supported With the HeartMate 3 Ventricular Assist Device

Abstract: There is a growing population of pediatric and adult patients supported with the HeartMate 3 ventricular assist device (HM3 VAD) all of whom require anticoagulation. Apixaban is an anticoagulant requiring less testing than warfarin which has been shown to be effective in other indications. We report five pediatric and young adult patients managed on HM3 VAD with apixaban anticoagulation for 1589 days of VAD support between January 6, 2019 and January 7, 2022. The median age was 17 years and the weight was 69 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…While our center can receive same day results for apixaban levels, we do realize that is not an option at all institutions. The described prophylactic and therapeutic apixaban levels have been demonstrated to have appropriate efficacy, safety, and low events rates in an analysis 219 pediatric patients, along with five HM3 VAD patients, from our institution, 17,18 along with a large meta-analysis in adults. 19 It has been demonstrated that chromogenic anti-factor Xa assay calibrated with heparin standards shows a correlation between apixaban levels and LMWH levels.…”
Section: Discussionmentioning
confidence: 94%
“…While our center can receive same day results for apixaban levels, we do realize that is not an option at all institutions. The described prophylactic and therapeutic apixaban levels have been demonstrated to have appropriate efficacy, safety, and low events rates in an analysis 219 pediatric patients, along with five HM3 VAD patients, from our institution, 17,18 along with a large meta-analysis in adults. 19 It has been demonstrated that chromogenic anti-factor Xa assay calibrated with heparin standards shows a correlation between apixaban levels and LMWH levels.…”
Section: Discussionmentioning
confidence: 94%
“…This finding has to be interpreted with caution due to the fact that no data on anticoagulation were analyzed and because there are known differences between anticoagulation protocols in Europe, even when using the same device [ 26 ]. In a recently published study, apixaban, together with low-dose aspirin, was safe and effective in children supported with an HM3 device [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since our initial report, there have been other small series reporting similar excellent outcomes. 1 As noted by Mahr, 2 and why we chose Apixaban for our patients, there are potential advantages to Apixaban over other direct oral anticoagulants to account for its success. Apixaban is now our standard of care.…”
Section: To the Editormentioning
confidence: 94%